The alveolar immune cell landscape is dysregulated in checkpoint inhibitor pneumonitis - Suresh, Karthik (J Clin Invest, 2019)
BACKGROUND: Checkpoint inhibitor pneumonitis (CIP) is a highly morbid complication of immune checkpoint immunotherapy (ICI), one which precludes the continuation of ICI. Yet, the mechanistic underpinnings of CIP are unknown. METHODS: To better understand the mechanism of lung injury in CIP, we prospectively collected bronchoalveolar lavage (BAL) samples in ICI-treated patients with (n = 12) and without CIP (n = 6), prior to initiating first-line therapy for CIP (high-dose corticosteroids). We analyzed BAL immune cell populations using a combination of traditional multicolor flow cytometry gating, unsupervised clustering analysis, and BAL supernatant cytokine measurements. RESULTS: We found increased BAL lymphocytosis, predominantly CD4(+) T cells, in patients with CIP. Specifically, we observed increased numbers of BAL central memory T cells, evidence of type I polarization, and decreased expression of cytotoxic T lymphocyte–associated protein 4 and programmed cell death protein 1 in BAL Tregs, suggesting both activation of proinflammatory subsets and an attenuated suppressive phenotype. CIP BAL myeloid immune populations displayed enhanced expression of IL-1β and decreased expression of counterregulatory interleukin-1 receptor antagonist. We observed increased levels of T-cell chemoattractants in the BAL supernatant, consistent with our proinflammatory, lymphocytic cellular landscape. CONCLUSION: We observe several immune cell subpopulations that are dysregulated in CIP, which may represent possible targets that could lead to therapeutics for this morbid immune-related adverse event. FUNDING: NIH, Department of Defense, and the Bloomberg~Kimmel Institute for Cancer Immunotherapy.